2018
DOI: 10.1080/15384047.2018.1480296
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape and clonal diversity of pulmonary adenoid cystic carcinoma

Abstract: Pulmonary adenoid cystic carcinoma is a rare and indolent lung malignancy, characterized by a protracted but unpredictable growth behavior. Currently, the treatment of PACC relies on surgery and local radiotherapy. However, treatment options for advanced PACC patients are limited. A larger number of studies demonstrated that advanced PACC patients obtained limited benefit from chemotherapy. Moreover, only a few case reports revealed PACC patients were candidates for target therapy. Therefore, there is an urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Occasional tumors focally expressed higher levels of PD-L1 or PD-L2. These results, in conjunction with the overall relatively low mutational burden of ACC, 20,22,28,29 suggest that although a small subset of tumors may have the potential to respond to checkpoint inhibitors, most will not. The CPS for PD-L1, on the other hand, revealed that 57% of tumors had scores of =1, which in clinical practice would indicate that up to 57% could be eligible for treatment with checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…Occasional tumors focally expressed higher levels of PD-L1 or PD-L2. These results, in conjunction with the overall relatively low mutational burden of ACC, 20,22,28,29 suggest that although a small subset of tumors may have the potential to respond to checkpoint inhibitors, most will not. The CPS for PD-L1, on the other hand, revealed that 57% of tumors had scores of =1, which in clinical practice would indicate that up to 57% could be eligible for treatment with checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…Developed surgical and anesthesiological procedures would make even wide tumors resectable. Contraindications to surgery include mediastinal lymph nodes, vascular involvement, tracheal invasion for more than 50% of its length, and distant metastases [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA concentration was measured using the Qubit dsDNA HS Assay kit on a Qubit Fluorometer 3.0 (Life Technologies, Carlsbad, CA, USA). The threshold of input DNA quantity was 200 ng for samples to be processed further for library preparation using the OncoScreen Panel covering 295 key genes (Burning Rock Biotech Ltd, Guangdong, China) as previously described 15,16 . Fragments between 200 and 400 bp were purified by AGEcout AMPure beads (Beckman Coulter, Pasadena, CA, USA).…”
Section: Methodsmentioning
confidence: 99%